Grit After Acl Reconstruction: Sex Differences and Association with Knee Outcomes Among Adolescent Athletes. Issue 5 (31st May 2022) - Armento, Aubrey; Logterman, Stephanie; Gagliardi, Alexia; Hovater, Whitney; Howell, David; Albright, Jay
Background: Grit reflects perseverance for pursuing long-term goals. Recovery from ACL reconstruction requires a long and challenging rehabilitation process. While grit has previously been used to predict success in education and military settings, little is known about the association between grit and the rehabilitation process among adolescent athletes after ACL reconstruction. Purpose: The primary aim of the study was to determine differences in GRIT-S scores between male and female athletes pre-operatively to 6 months post-ACL reconstruction. The second aim of the study was to assess the relationship between pre-operative GRIT-S scores and knee outcome measures 6 months post-operatively. Methods: All participants completed the GRIT-S questionnaire, the Pediatric International Knee Documentation Committee (Pedi-IKDC) subjective knee form, and the Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS) at a pre-operative appointment and then again approximately 6 months after ACL reconstruction. We conducted a linear mixed model analysis to assess the effects of sex and time on GRIT-S scores. We then conducted a linear regression analysis to determine if pre-operative GRIT-S scores predicted IKDC and HSS Pedi-FABS scores at 6 months post-operatively. We defined statistical significance as p < 0.05. Results: We included 83 participants (mean age 16.0 +/- 2.3 years, 70% female) from a prospective registry of pediatric athletes undergoing ACL reconstruction by one surgeon at a single institution. For the entire study population, there was no statistically significant change in GRIT-S scores from the pre-operative assessment to 6 months post-operatively. However, there was a statistically significant effect of sex (p=0.03) on GRIT-S scores from pre-operative assessment to 6 months post-operatively, with female athletes demonstrating more grit than male athletes across both assessments (Figure 1). Additionally, there was no significant association between pre-operative GRIT-S scores and Pedi-IKDC and HSS Pedi-FABS scores 6 months post-operatively for the entire group (Figure 2). Conclusion: In our study population, female athletes reported higher GRIT-S scores than male athletes across the first 6 months of rehabilitation after ACL reconstruction. Pre-operative GRIT-S scores do not appear to be significantly associated with knee outcome measures 6 months post-operatively, which could suggest that grit may not necessarily predict success in the rehabilitation process after ACL reconstruction. However, future studies will examine how grit is associated with return-to-sport outcomes to determine if grit is a useful marker in predicting successful return-to-sport after ACL reconstruction in adolescent athletes. Figure 1. Mean GRIT-S scores (error bars represent 95% confidence intervals) for male and female athletes at the pre-operative visit and approximately 6 months following surgery. Figure 2. Scatterplot and line of best fit describing the relationship between pre-operative GRIT-S scores and Pedi-IKDC (knee function) and HSS Pedi-FABS (activity level) scores at approximately 6 months following surgery.